Human liver stem cell‐derived microvesicles accelerate hepatic regeneration in hepatectomized rats - Herrera, M. B.; Fonsato, V.; Gatti, S.; Deregibus, M. C.; Sordi, A.; Cantarella, D.; Calogero, R.; Bussolati, B.; Tetta, C.; Camussi, G. (Journal of cellular and molecular medicine, 2010)
Several studies indicate that adult stem cells may improve the recovery from acute tissue injury. It has been suggested that they may contribute to tissue regeneration by the release of paracrine factors promoting proliferation of tissue resident cells. However, the factors involved remain unknown. In the present study we found that microvesicles (MVs) derived from human liver stem cells (HLSC) induced in vitro proliferation and apoptosis resistance of human and rat hepatocytes. These effects required internalization of MVs in the hepatocytes by an α4‐integrin‐dependent mechanism. However, MVs pre‐treated with RNase, even if internalized, were unable to induce hepatocyte proliferation and apoptosis resistance, suggesting an RNA‐dependent effect. Microarray analysis and quantitative RT‐PCR demonstrated that MVs were shuttling a specific subset of cellular mRNA, such as mRNA associated in the control of transcription, translation, proliferation and apoptosis. When administered in vivo, MVs accelerated the morphological and functional recovery of liver in a model of 70% hepatectomy in rats. This effect was associated with increase in hepatocyte proliferation and was abolished by RNase pre‐treatment of MVs. Using human AGO2, as a reporter gene present in MVs, we found the expression of human AGO2 mRNA and protein in the liver of hepatectomized rats treated with MVs. These data suggested a translation of the MV shuttled mRNA into hepatocytes of treated rats. In conclusion, these results suggest that MVs derived from HLSC may activate a proliferative program in remnant hepatocytes after hepatectomy by a horizontal transfer of specific mRNA subsets.